A new species, Russula luteolamellata (Russulaceae, Russulales) from China - Zhou, Hao; Cheng, Guiqiang; Hou, Chenglin (Phytotaxa, 2022)
A new species of Russula subgenus Brevipedum, Russula luteolamellata, is described from the Yanshan Mountains in northern China based on morphology and phylogenetic analysis of the nrITS and nrLSU-RPB2-mtSSU gene regions. Russula luteolamellata is characterized by the yellowish to pale orange pileus, white to yellowish lamella with a few rust-colored spots at the margin, a low density of warts on the basidiospores, and pileocystidia that turn gray in sulfovanillin. Detailed morphological and habitat comparisons of Chinese species in subgenus Brevipedum are given.